2018
DOI: 10.1093/neuros/nyy192
|View full text |Cite
|
Sign up to set email alerts
|

Four-Dimensional Flow MRI Analysis of Cerebral Blood Flow Before and After High-Flow Extracranial–Intracranial Bypass Surgery With Internal Carotid Artery Ligation

Abstract: After high-flow EC-IC bypass with permanent ICA ligation, the bypass artery could partially compensate for the loss of BFV of the sacrificed ICA. The increased flow of the contralateral ICA and BA supply collateral blood flow. Clinically irrelevant hyperperfusion was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…However, limitations of the study included no comparison to a ‘gold-standard’ technique, uniform v enc , long scan times and poor flow extraction of small vessels. A similar study was carried out by the same group in 2019 to assess arterial blood flow before and after carotid bypass surgery, 39 in which undersampling techniques reduced the scan time to just six minutes, yet issues with low spatial resolution continued to limit the evaluation of small arteries.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, limitations of the study included no comparison to a ‘gold-standard’ technique, uniform v enc , long scan times and poor flow extraction of small vessels. A similar study was carried out by the same group in 2019 to assess arterial blood flow before and after carotid bypass surgery, 39 in which undersampling techniques reduced the scan time to just six minutes, yet issues with low spatial resolution continued to limit the evaluation of small arteries.…”
Section: Resultsmentioning
confidence: 98%
“…Several studies demonstrated the use of 4D flow in the context of surgical operations. 38,39 These are useful in highlighting and summarising the main concerns in using 4D flow in disease research, and the solutions that will likely address these concerns in the future: including (but not limited to) high-field MRI, advanced acceleration techniques (ideally using correlations in space and time), increased resolution and multi- v enc acquisition. A summary of the range of popular imaging parameters used in current, state-of-the-art cerebral 4D flow studies is presented in Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…Their work importantly characterized the limitations of 4D flow to evaluate small arteries (<2.4 mm in their study) and illustrated the feasibility of the technique in this patient population. In addition, Orita et al continued to expand the scope of 4D flow in EC‐IC bypass by characterizing the hemodynamic changes that occurred after bypass, by measuring both preoperative and postoperative flow measurements in bypass patients who also underwent ICA ligation 19 . Using 4D flow, they were able to quantify the degree to which the bypass graft could compensate for the sacrificed ICA in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of vessel patency and blood flow direction is critical in various medical situations, including diagnosis and treatment monitoring of ischemic diseases [1][2][3][4][5][6][7][8] and image-guided vascular surgeries. [9][10][11][12][13][14][15][16][17][18][19][20][21] Ischemic diseases are typically characterized by the disruption of the blood flow, such as changes in blood flow speed and blood flow direction. 11 In the treatment of ischemic diseases, the natural and procedurally promoted vascular remodeling of existing arterial interconnections to form adequate collateral development for restoration of perfusion to the organs that have suffered ischemia is closely related to the patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Non-invasive monitoring of blood flow direction and occasional flow direction reversal in the treatment of ischemic diseases can provide important information to assess therapeutic effectiveness. [1][2][3][4][5] In various vascular surgeries such as vascular bypass, [13][14][15][16][17] vascular shunt, 5,[18][19][20][21] and aneurysm surgery, 9,10,14,17 blood flow characteristics such as blood flow path and blood flow direction are intentionally modified. Imaging the blood flow direction during the surgeries that confirms the intended changes of the paths and directions of the blood flow while avoiding any unintended alteration in vessel patency and blood flow direction is highly desirable for monitoring of the immediate effects of the surgery and for quality control of the vascular intervention.…”
Section: Introductionmentioning
confidence: 99%